ANALISIS PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA PT UNIVERSAL FOOTWEAR UTAMA INDONESIA AKIBAT KEPAILITAN PERUSAHAAN BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS PUTUSAN NOMOR 12/PDT.SUS-PKPU/2016/PN. NIAGA.JKT.PST) - Marchel Thobie; Ariawan Gunadi (Jurnal Hukum Adigama, 2019)
The  case faced in  writing  this scientific paper is how  the legal protection of the workers     of  PT Universal Footwear Utama Indonesia who were declared bankrupt in Decision No.               12/Pdt.Sus-PKPU/2016/PN.Niaga. Jkt Ps t who have not paid salaries for 3 months and severance pay until now in 2018   and   how  the   responsibility  of  the curator for the bankruptcy of PT Universal Footwear Utama  Indonesia  after auctioning off the auction for salaries and severance labor. The research  method  used  in  this  study is  normative  legal  research. The results showed that the legal protection of the workers of PT Universal Footwear Utama Indonesia who were declared bankrupt in Decision  No. 12/Pdt.Sus-PKPU /2016/PN.Niaga/Jkt.Pst  who have not paid salaries for 3 months and severance pay until now in 2018, in principle all wages of arrears of workers (employee salaries) must be paid after the assets  of  the bankrupt Debtor have sold and the  Distribution  list has  been  determined   by  the  Court  on the proposal of the curator.        The responsibility of the curator for the bankruptcy of PT Universal Footwear Utama Indonesia after the bankruptcy of the auction was sold against the salary and severance of employment                 was   based   on   Article 74 of  the Bankruptcy Act.  The task of the curator is to share the proceeds of the sale of bankruptcy to the creditors in the order (their respective ranks